Pengembangan Game Edukasi Bertema Doraemon Berbasis Canva pada Mata Pelajaran Bahasa Indonesia Kelas III SDN 1 Tawing: Penelitian - Suci Anjar Yanti; Nugrananda Janattaka (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This development research is motivated by the scarcity of digital-based learning media, which results in a monotonous learning experience similar to conventional approaches. The objective of this development is to create an educational Game themed around Doraemon using Canva for Indonesian language lessons for third-grade students studying Chapter 6: I'm Lost. The framework used in this research is the ADDIE model, which includes the phases of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques include observation, questionnaires, and documentation. Instruments include validation questionnaires and student responses. Based on the research findings, the Doraemon-themed educational Game created using Canva received a validity rating of 92% from media experts 1 and 2, and 95% from subject matter experts. Student responses in the questionnaire yielded a percentage of 95%. Therefore, the Doraemon-themed educational Game designed using Canva is highly suitable and effective as a technology-based learning medium for third-grade students at SDN 1 Tawing.